(untitled) (UNIZIK Journal of Marketing, 2024)
There is high demand for marketing graduates because marketing is the engine that drives every economy. Unfortunately, many marketing graduates in Nigeria are unable to gain and retain employment for marketing-related functions because of weak knowledge of marketing education. The objective of this study is to examine the impact of learning management tools for executing marketing education in Nigeria universities. To realize this objective, the Descriptive research design was adopted. A structured questionnaire was administered through online Google Form to 87 respondents selected from a population of 112 students in the department of Business Management and Marketing of Baze University Abuja. Data obtained was analyzed with descriptive statistics. The findings reveal that: learning management tools such as Google Classroom streaming and Emails have very effective impact on marketing education, while Google Turnitin and classwork have low impact on marketing education; and environmental factors such as faulty devices, Network connectivity problems, attitude of students and Noise affect the execution of digital marketing education. The study recommends that higher institutions should emphasis more on the utilization of Google Classroom streaming and Google email interaction and ensure steady and cheap internet connectivity of digital education tools